Proceedings of the 2021 5th International Seminar on Education, Management and Social Sciences (ISEMSS 2021) 2021
DOI: 10.2991/assehr.k.210806.107
|View full text |Cite
|
Sign up to set email alerts
|

Oral English in China

Abstract: Many Chinese students begin to learn English as a main subject in primary schools. They focus on the written English while ignore the oral part, because a long-term exploration of traditional teaching makes them believe that test paper score is the ultimate goal. Students have few opportunities to practice their oral English. The situation leads to stagnant, even receded, oral English skills. Therefore, it is a challenge that how to help students to develop their oral English. This paper aims to analyze this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The majority of English teachers' oral English proficiency is at a lower level than what level they should be [3]. A number of teachers even indicated that they can neither express themselves accurately in English, nor communicate with English speakers in daily dialogues [6]. On the one hand, phonetic errors might challenge these teachers.…”
Section: The Insufficient Level Of Professional Quality Of English Te...mentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of English teachers' oral English proficiency is at a lower level than what level they should be [3]. A number of teachers even indicated that they can neither express themselves accurately in English, nor communicate with English speakers in daily dialogues [6]. On the one hand, phonetic errors might challenge these teachers.…”
Section: The Insufficient Level Of Professional Quality Of English Te...mentioning
confidence: 99%
“…Shan suggested that organizing effective oral interaction activities is beneficial to creating positive English communication environments, which could possibly reduce the anxiety of students while speaking English and encourage students to actively participate in the activities [5]. Nevertheless, the ability to conduct efficient activities is precisely what the majority of Chinese English teachers lacked [6].…”
Section: The Insufficient Level Of Professional Quality Of English Te...mentioning
confidence: 99%
See 3 more Smart Citations